Does Hardiness Act as A Mediator in The Relationship between Social Support and Academic Stress? - Ma'sum, Nikmah Rafika; Aisyah, Siti; Siti Salmaniah Siregar, Nina (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
Final-year students often experience high academic pressure, especially during the process of writing their thesis. In such situations, social support and hardiness are important factors that can help students manage academic stress. This study aims to examine the effect of social support on academic stress with hardiness as a mediating variable among students who are currently writing their thesis at Universitas Medan Area. This research employed a quantitative method using the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS). The sample consisted of 250 students selected through purposive sampling. The instruments used were the adapted versions of the Academic Stress Scale (ASS), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Revised Academic Hardiness Scale (RAHS). The results showed that social support had a negative effect on academic stress (β = -0.318, p < 0.05), hardiness had a negative effect on academic stress (β = -0.496, p < 0.05), and social support had a positive effect on hardiness (β = 0.440, p < 0.05).Mahasiswa tingkat akhir menghadapi tekanan akademik yang tinggi terutama saat menyusun skripsi. Dalam situasi tersebut dukungan sosial dan hardiness menjadi faktor penting yang dapat membantu mahasiswa mengelola stres akademik. Penelitian ini bertujuan untuk mengetahui pengaruh dukungan sosial terhadap stres akademik dengan hardiness sebagai variabel mediasi pada mahasiswa yang sedang menyusun skripsi di Universitas Medan Area. Penelitian ini diterapkan dengan metode kuantitatif menggunakan pendekatan Structural Equation Modeling (SEM) berbasis Partial Least Squares (PLS). Jumlah sampel sebanyak 250 mahasiswa yang dipilih melalui teknik purposive sampling. Instrumen yang digunakan terdiri dari Academic Stress Scale (ASS), Multidimensional Scale of Perceived Social Support (MSPSS), dan Revised Academic Hardiness Scale (RAHS) yang telah diadaptasi. Hasil penelitian menunjukkan bahwa dukungan sosial berpengaruh negatif terhadap stres akademik (β = -0.318, p < 0.05), hardiness berpengaruh negatif terhadap stres akademik (β = -0.496, p < 0.05), dan dukungan sosial berpengaruh positif terhadap hardiness (β = 0.440, p < 0.05). Selain itu, hardiness terbukti memediasi secara signifikan hubungan antara dukungan sosial dan stres akademik (β = -0.218, p < 0.05). Temuan ini menegaskan bahwa dukungan sosial dan hardiness memainkan peran penting dalam menurunkan tingkat stres akademik mahasiswa tingkat akhir.